Inovasi SD Muhammadiyah 5 Surakarta Dalam Mewujudkan Sekolah Kondusif - SIDIQ, ASAF; , Drs Suwarno, SH., M.Pd (2017)
This research aims to understand the innovation that is in primary schools Muhammadiyah 5 Surakarta in creating a conducive school. The type of this research is qualitative research with case study approacth. The data source of this research is principal and teachers. Data collection techniques were used interviews, observation and documentation. Data validity of this research used triangulation. Data were analyzed interactivly consisting of data collection, data reduction, data display, and conclusion and verification. The results of this study indicate that there are innovations in SD Muhammadiyah Surakarta 5 in creating a conducive school, namely: (1) Shaking hands with the students every morning. (2) Duha prayer. (3) Memorizing short letter in musola led the teachers picket. (4) Meetings and motivation morning. (5) The reading and literacy Iqro morning. (6) Students pray will eat before the break. (7) line up the students before class is accompanied by reading the prayer after meals. (8) dhuhur prayer congregation. (9) Evaluation of lunch if any important info. (10) The establishment of picket schedule. (11) Enforcement of regulations teachers and students. (12) Working cleaning the mosque.